Analisis Kepuasan Pelanggan pada Platform Netflix di Kota Bandung dengan Menggunakan Metode Customer Satisfaction Index (CSI) dan Importance Performance Analysis (IPA) - Dea Shafa Adilah; Indra Fajar Alamsyah; Rizka Estisia Pratiwi (UNISBA Press, 2024)
Abstract. The rapid growth of streaming services in Indonesia has led to increasingly intense competition in the industry. Netflix, as one of the popular streaming services, must continuously innovate to maintain its position. To remain competitive with other players in the same business environment, a study was conducted. The purpose of this study is to determine the level of customer satisfaction with Netflix's service quality and to assess the alignment between the service quality attributes that customers expect and what Netflix provides. The sampling technique used in this study is saturated sampling. The research method utilizes the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA) methods. The results of the Customer Satisfaction Index (CSI) indicate a score of 86.19%, which falls into the